Antibodies Recognizing Yersinia enterocolitica Lipopolysaccharides of Various Chemotypes in Synovial Fluids From Patients With Juvenile Idiopathic Arthritis - Katarzyna Kasperkiewicz; Anna S. Świerzko; Mateusz Michalski; Łukasz Eppa; Mikael Skurnik; Zbigniew Żuber; Maciej Cedzyński (Journal of Immunology Research)
Yersinia enterocolitica O:3 (YeO3) is considered to be associated with reactive arthritis (ReA), and its lipopolysaccharide (LPS) has been detected in synovial fluids from patients. Interestingly, YeO3 wild-type LPS was processed by host cells, resulting in truncated LPS molecules presenting the core region. Previously, we reported the immunogenicity but not adjuvanticity of YeO3 LPSs of wild (S) type, Ra, Rd, or Re chemotypes in mice. Here, we demonstrate the presence of YeO3 LPS chemotype-specific antibodies in all analyzed synovial fluids (SF) from patients with juvenile idiopathic arthritis (JIA). Interestingly, the high titer of antibodies specific for the Kdo-lipid A region was found in most tested SF. In contrast, only a few were positive for antibodies recognizing O-specific polysaccharides. Western blot analysis revealed the presence of antibodies reacting with fast-migrating LPS fractions and enterobacterial common antigen (ECA) in synovial fluid samples. Our data also suggest the importance of LPS-associated ECA for the antigenicity of endotoxin. Furthermore, we confirmed in vitro that Yersinia LPS processing leads to the exposure of its core region and enhanced potency of complement lectin pathway activation.